The Impact of Depression and Dietary Practices on Polycystic Ovarian Syndrome Among Females of Northern Punjab, Pakistan - Bareera Eman; Allah Rakha; Iahtisham-Ul-Haq; Urwa Tariq; Muqadas Zia; Ayesha Saddiqa (RADS Journal of Biological Research & Applied Science, 2024)
Background: Polycystic Ovary Syndrome (PCOS) is a hormonal disorder affecting women of reproductive age, characterized by dysmenorrhea, amenorrhea, hyperandrogenism and cystic ovaries.